White Paper: Radiological Curriculum for Undergraduate Medical Education in Germany - Ertl-Wagner, B.; Barkhausen, J.; Mahnken, A. H.; Mentzel, H. J.; Uder, M.; Weidemann, J.; Stumpp, P.; German Association of Chairmen in Academic Radiology (KLR); Adam, G.; Antoch, G.; Beer, M.; Bley, T.; Bücker, A.; Düber, C.; Forsting, M.; Hamm, B.; Hauenstein, K.; Heindel, W.; Hosten, N.; Jansen, O.; Kahn, T.; Kauczor, H. U.; Krombach, G.; Kuhl, C.; Langer, M.; Laniado, M.; Lotz, J.; Mahnken, A.; Maintz, D.; Nikolaou, K.; Reiser, M.; Ricke, J.; Rummeny, E.; Schild, H.; Schönberg, S.; Spielmann, R. P.; Stroszczynski, C.; Teichgräber, U.; Vogl, T. J.; Wacker, F.; German Roentgen Society (DRG); Vorwerk, D.; Anton, F.; Neumann, S.; Lohwasser, S. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Radiology represents a highly relevant part of undergraduate medical education from preclinical studies to subinternship training. It is therefore important to establish a content base for teaching radiology in German Medical Faculties.Materials and Methods: The German Society of Radiology (DRG) developed a model curriculum for radiological teaching at German medical universities, which is presented in this article. There is also a European model curriculum for undergraduate teaching (U-level curriculum of the European Society of Radiology). In a modular concept, the students shall learn important radiological core principles in the realms of knowledge, skills and competences as well as core scientific competences in the imaging sciences.Results: The curriculum is divided into two modules. Module 1 includes principles of radiation biology, radiation protection and imaging technology, imaging anatomy as well as the risks and side effects of radiological methods, procedures and contrast media. This module is modality-oriented. Module 2 comprises radiological diagnostic decision-making and imaging-based interventional techniques for various disease entities. This module is organ system-oriented.Conclusion: The curriculum is meant as a living document to be amended and revised at regular intervals. The curriculum can be used as a basis for individual curricular development at German Medical Faculties. It can be integrated into traditional or reformed medical teaching curricula.Key Points:• Radiology is an integral and important part of medical education.• The German Society of Radiology (DRG) developed a model curriculum for teaching radiology at German Medical Faculties to help students develop the ability to make medical decisions based on scientific knowledge and act accordingly.• This curriculum can be used for individual curricular development at medical departments. It is divided into two modules with several chapters.Citation Format:• Ertl-Wagner B, Barkhausen J, Mahnken AH et al. White Paper: Radiological Curriculum for Undergraduate Medical Education in Germany. Fortschr Röntgenstr 2016; 188: 1017 – 1023
Keywords: medical education; undergraduate teaching; curriculum; competence-based learning; radiological teaching